Evaluation of the medical assistance to asthmatic patients. - Margarita Roméu Escobar; Milagros Mesa Abreu; Caridad Hernández Gutiérrez; Estrella Armenteros Espinosa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: The evaluation and perfeccioning of assistance quality in Health services are objectives of permanent interest. Bronquial asthma is a high frequency desease, and it requires an evaluated attention. Objective: to evaluate the medical attention to the asthmatic patient in the Area III polyclinic of Cienfuegos. Methods: Transversal and descriptive study that included 150 patients randomly selected from the dispensary records of the Area III Educational Polyclinic of Cienfuegos, in December 2001. Medical records were checked and the patients were interviewed. Results: differences were found among the classifications (light, persistent and moderate) reflected in medical records and the evaluation the authors made. Only 12 % of the Medical Records had good quality. The 80 % of patients have adequate knowledge about their desease, but most of them do not follow inter-crisis treatment. The place more used for treatment of the crisis was the polyclinic. There is a high level of satisfaction with medical services. Conclusion: The medical care of patient with bronchial asthma can be improved, being more systematic in inter-crisis treatment based on previous evaluation of each patient and in the sequential use of different therapeutic options, particularly in the practice of correct life styles.